PENUNDAAN PEMBAGIAN WARISAN PADA MASYARAKAT MUSLIM DI KOTA LANGSA - Lia Dahliani; Faisar Ananda; Ansari Yamamah (TAHKIM, 2018)
There are several ways that the Muslim community in solving the problem of division of inheritance in the city of Langsa, that is by way of musyawarah or kinship both involve family or even involving the village device, and the last way is through the Court Syar'iyah Langsa. Many Langsa city residents are procrastinating their inheritance. Factor or reason Langsa City society postpone the division of inheritance that is: agreement of all heirs; the heirs of many who are young or have not yet been given an inheritance; some parties want to take possession of the estate so that there is no or delayed distribution of the inheritance; most societies consider discussing inheritance after heirs are taboo; still life of one of the father or mother of the heir so that postponed the division of inheritance. The impact of delay in distribution of inheritance made by the community in Langsa City, as follows: conflict between the heirs, whether mild conflict to severe conflict; the existence of reduced heirs rights of the part which should be accepted; the existence of heirs who can not feel the inheritance due to death before the inheritance had been distributed; the breaking of the relationship or the brotherhood between the heirs due to the seizure of inheritance.